(untitled) (Veterinary Science Development, 2017)
No previous reports have compared the suitability of expanded polytetrafluoroethylene (ePTFE) and polypropylene as artificial suture materials for chordal reconstruction in mitral valve plasty (MVP) in the dog. Twelve normal dogs were subjected to MVP using surfaceinduced deep hypothermia. In the short-term group (1.5-4 months after surgery), all ePTFE sutures were covered by a tissue sheath including the paired suture arms, which gave the appearance of native chordae from 2 months after surgery. In contrast, all polypropylene sutures were not covered by tissue, and appeared the same as the paired polypropylene suture arms at the operation. In the long-term group (12 months after surgery), all ePTFE sutures were covered by a tissue sheath, which appeared the same as that in the short-term group, and had flexibility without increased thickness with time. In contrast, although the polypropylene suture was covered completely by a tissue sheath in 1 dog, all the other polypropylene sutures were exposed except for both ends of the suture. ePTFE may be superior to polypropylene as an artificial suture material for chordal reconstruction in MVP.